Fostering an effective organizational relationship between management and employees: A co-operative arrangement would promote the achievement of goals, and the delivery of projected products and services. - Kwadade-Cudjoe, Francis (Archives of Business Research, 2020)
A good relationship between management and employees within an organization has always been the best ingredient every entity should aspire for. Management alone cannot run the organization, and similarly, employees. There is therefore, the need for good rapport to exist between them for a successful management of the organization. The functions of management are quite distinct from employees, and similarly that of employees. When an organization is not able to achieve its goals / objectives, both management and employees would suffer, as they would lose their jobs. Management, as leaders of the organization, must make sure there is harmony within the organization for the achievement of goals. It is good idea for a union to be set up within the organization to enable good communication amongst the employees, but not to coerce management for unnecessary demands. Similarly, management should not threaten the employees with unnecessary dismissals. There is the need for good formulation of policies, strategies and conditions of service for effective administration of the organization.